Prevalence of anemia in pregnant women, study CS "Horacio Zevallos." - Rodríguez, Javier (2015)
OBJECTIVE: To determine the prevalence of anemia in pregnant women, their relationship to low birth weight and some characteristics of mothers. MATERIALS AND METHODS: A cross-sectional study where a total of 84 pregnant women between 13 and 45 years attending the CS "Horacio Zevallos" during 1999. L was performed was studied anemia was considered when lower levels of 11 g / found hemoglobin. RESULTS: The prevalence of anemia among pregnant women was 33.3% with an average hemoglobin level of 10.9 gl / L. Mild anemia was the most common (85.7%), followed by moderate (14.2%). Prevalence of anemia was slightly higher in women over 35 years and did not vary according to the level of education or the birth interval. The average weight of newborns was 3120 g. The main risk factors for anemia were poor nutrition, inadequate sanitation and low socioeconomic status. CONCLUSIONS: The prevalence of anemia in pregnant women in Horacio Zevallos CS is high, but was not associated with low birth weight of newborns or with perinatal mortality.